2018
DOI: 10.3389/fcvm.2018.00107
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Alterations in Oxidant and Anti-Oxidant Enzymes in the Vascular System

Abstract: Cardiovascular diseases (CVD) are one of the prime causes of mortality worldwide. Experimental animal models have become a valuable tool to investigate and further advance our knowledge on etiology, pathophysiology and intervention. They also provide a great opportunity to understand the contribution of different genes and effector molecules in the pathogenesis and development of diseases at the sub-cellular levels. High levels of reactive oxygen species (ROS) have been associated with the progression of CVD s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 124 publications
(277 reference statements)
4
28
0
Order By: Relevance
“…Myocardium contains a variety of specific enzymes, and once myocardial damage or necrosis, these enzymes are released into serum in different degrees, thus measuring the activity of these enzymes in serum to diagnose and monitor MI [25]. The study found that serum levels of AST, LDH, and cTn-T were significantly increased in ISO-treated mice, clearly suggesting that ISO-induced myocardial damage, which is consistent with previous reports [26].…”
Section: Discussionsupporting
confidence: 88%
“…Myocardium contains a variety of specific enzymes, and once myocardial damage or necrosis, these enzymes are released into serum in different degrees, thus measuring the activity of these enzymes in serum to diagnose and monitor MI [25]. The study found that serum levels of AST, LDH, and cTn-T were significantly increased in ISO-treated mice, clearly suggesting that ISO-induced myocardial damage, which is consistent with previous reports [26].…”
Section: Discussionsupporting
confidence: 88%
“…Our finding was in line with the study by Rindler who reported a significant increase in CAT activity in mouse fed with a high-fat diet, for 2 to 30 weeks (Rindler et al, 2013). Indeed, overexpression of CAT has been shown to be beneficial in preventing oxidative damage (Awad, Aldosari & Abid, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…The most abundant cellular form of GPx is GPx-1. GPx-1 deficiency has been linked to the development of endothelial dysfunction, inflammation, and neointimal formation [ 77 ]. The role of GPx-1 has been demonstrated in the normalization of VSMC proliferation rate through the inhibition of matrix metalloproteinase 9 (MMP9), and the consequent restoring of the endothelial function [ 73 ].…”
Section: Oxidative Stress and Endothelial Dysfunction And Cvdmentioning
confidence: 99%